2019
DOI: 10.20945/2359-3997000000113
|View full text |Cite
|
Sign up to set email alerts
|

Is thyroid nodule volume predictive for malignancy?

Abstract: Objective: We aimed to determine the roles of preoperative thyroid nodule diameter and volume in the prediction of malignancy. Subjects and methods: The medical records of patients who underwent thyroidectomy between January 2007 and December 2014 were reviewed. The nodule diameters were grouped as < 1 cm, 1-1.9 cm, 2-3.9 cm and ≥ 4 cm, and volume was grouped as > 5 cm 3 , 5-9.9 cm 3 and > 10 cm 3. ROC (Receiver Operating Characteristic) curve analysis was performed to find the optimal cutoff value of diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
1
6
0
2
Order By: Relevance
“…Although a larger size has been reported as an independent predictor of malignancy [3,37,41], the relationship between nodule size and risk of thyroid cancer remains uncertain. In concordance with the results of other studies [42][43][44][45], we observed that benign thyroid nodules were significantly larger than malignant nodules, and that the risk of thyroid cancer was inversely related to the largest nodule diameter. Even more relevant, benign lesions were more frequently oval-shaped and parallel-oriented.…”
Section: Discussionsupporting
confidence: 92%
“…Although a larger size has been reported as an independent predictor of malignancy [3,37,41], the relationship between nodule size and risk of thyroid cancer remains uncertain. In concordance with the results of other studies [42][43][44][45], we observed that benign thyroid nodules were significantly larger than malignant nodules, and that the risk of thyroid cancer was inversely related to the largest nodule diameter. Even more relevant, benign lesions were more frequently oval-shaped and parallel-oriented.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our study, many studies did not identify a linear relationship between increasing nodule size 4 cm and risk of malignancy, with some studies reporting a lower rate of malignancy in nodules 4 cm compared to nodules <4 cm. 5,6,8,23 The false-negative rate in larger nodules is also debated; a recent study by Kizilgul and colleagues found no significant difference between nodules <4 cm versus 4 cm, while a study by Bestepe et al cited greater than a 2-fold increase in false-negative FNAB for larger nodules. 6,9 While the overall false-negative rate in our study was consistent with or lower than the rates cited by many large studies and meta-analyses, these other studies did not incorporate patient age.…”
Section: Discussionmentioning
confidence: 99%
“…Ayrıca belirsiz sitolojiye sahip, tek taraflı nodülü olan çocuklarda lobektomi uygulandı. Literatürde nodül büyüklüğü yada hacmiyle malignite arasındaki ilişki ile ilgili yapılan hemen hemen tüm çalışmalar nodül çapını boyut parametresi olarak değerlendirmiştir (7). Ancak bu çalışmalar yetişkin yaş grubunda yapılmıştır.…”
Section: Discussionunclassified
“…Çalışmamız, çocuk yaş grubunda nodül hacmini bir nodülün üç çapının tümü kullanılarak hesaplanan ve boyut parametresi olarak değerlendiren ilk çalışmadır. Beştepe ve arkadaşlarının çalışmasında 10 cm 3 den büyük nodüllerin malignite oranın daha az olduğu, malign ve benign tümörlerde ortalama nodül hacminin ise benzer olduğu bildirilmektedir (7)…”
Section: Discussionunclassified